If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ab + -1c = d(c) Multiply d * c ab + -1c = cd Solving ab + -1c = cd Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'c' to each side of the equation. ab + -1c + c = c + cd Combine like terms: -1c + c = 0 ab + 0 = c + cd ab = c + cd Divide each side by 'b'. a = b-1c + b-1cd Simplifying a = b-1c + b-1cd
| y=2/5X-4/8 | | 3a+7=6a+5 | | 6n+3=6n-4 | | 4b-7-15b+3=0 | | 15=c | | (9/7)-(5/14)=s | | -6(3x+3)=34+8x | | 5x+5=-3[x-1] | | -1-7(1-2k)=90 | | -7/2u+7/3=-2/3u-6 | | 4x+1=-2x+5 | | 5a-y=c | | -8(-5+3r)=112 | | 5(3x-6)-3=5(x-3)+2 | | 6z+10+2z-1=7z+14 | | m+15=2m | | -75/15 | | 7a+16=32+4a | | (3/5)(2x+8y) | | 2x+-7=3 | | 55+(x+110)=(165+2x) | | -(x-10)= | | 2.10+(0.80x)=11.70 | | -(5x+4)-4x=8+6x | | -2+10+(-3)+5= | | x^2-25x-150=0 | | s=27.13 | | 3p+4(2p-7)=-116 | | 6x-(3x)+x-6= | | -7x-5=-4-(7x-6) | | 1/3(x-9)=x+9 | | 6-6B-8B=8(-7+8B) |